CURIOSITY AT THE CENTER OF ONE’S LIFE (Editor: J. Martin O’Hara) - Pedersen, Eigil (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1989)
J. Martin O’Hara, Editor. CURIOSITY AT THE CENTER OF ONE’S LIFE: STATEMENTS AND QUESTIONS OF R. ERIC O’CONNOR. Montreal: The Thomas More Institute; 1987. 589 pp. 40, Hardcover, 25, Paper.